2002
DOI: 10.7863/jum.2002.21.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sonographic Visualization of the Appendix With a Saline Enema in Children With Suspected Appendicitis

Abstract: Objective. To determine whether abdominal sonography after a saline enema can identify the appendix that is not visualized at graded compression sonography in children with suspected appendicitis. Methods. High-frequency compression sonography was prospectively performed in 120 consecutive children with suspected appendicitis; the appendix was not identified in 27 of these patients. Among the 27 patients with a nonvisualized appendix, abdominal sonography after a saline enema was performed in 12 to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Sources of heterogeneity among primary studies in our meta-analysis include variations in the institution type (eg, pediatric hospital, academic hospital, and community hospital), characteristics of the imaging modality, experience of sonographers, experience of imaging reviewers, handling of equivocal results, and criteria for diagnosis of appendicitis. Of note, five of nine studies (56%) on second-line US (32,33,35,37,38), 12 of 20 studies (60%) on CT (26,37,41,43,45,46,(48)(49)(50)(52)(53)(54), and six of 11 studies (55%) on MRI (24,56,59-62) did not state how equivocal results were handled. The remaining studies used a variety of strategies such as the use of a Likert scale, considering all equivocal results to be false-positive findings or false-negative findings, or excluding equivocal results from the 2 3 2 contingency table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of heterogeneity among primary studies in our meta-analysis include variations in the institution type (eg, pediatric hospital, academic hospital, and community hospital), characteristics of the imaging modality, experience of sonographers, experience of imaging reviewers, handling of equivocal results, and criteria for diagnosis of appendicitis. Of note, five of nine studies (56%) on second-line US (32,33,35,37,38), 12 of 20 studies (60%) on CT (26,37,41,43,45,46,(48)(49)(50)(52)(53)(54), and six of 11 studies (55%) on MRI (24,56,59-62) did not state how equivocal results were handled. The remaining studies used a variety of strategies such as the use of a Likert scale, considering all equivocal results to be false-positive findings or false-negative findings, or excluding equivocal results from the 2 3 2 contingency table.…”
Section: Discussionmentioning
confidence: 99%
“…When grouped by modality, there were nine articles on US, composed of six articles on 548 children (9,11,(32)(33)(34)(35) and three articles on 169 adults (36)(37)(38); 20 articles on CT, composed of nine articles on 1498 children (9,26,(39)(40)(41)(42)(43)(44)(45) and 11 articles on 1027 adults (25,37,(46)(47)(48)(49)(50)(51)(52)(53)(54); and 11 articles on MRI, composed of five articles on 287 children (39,(55)(56)(57)(58), one article on 223 adults (59), and five articles on 204 pregnant women (for a total of 427 patients) (24,(60)(61)(62)(63). Figure 1 shows the article selection process.…”
Section: Literature Search and Article Selectionmentioning
confidence: 99%
“…Bladder repletion is not necessary to allow optimal examination of appendix ( Figure 1) [22]. Some authors have shown improved visualization of the appendix using saling colonic enema: this option is however not applicable and commonly used in clinical routine [23].…”
Section: Exam Techniquementioning
confidence: 99%